2017
DOI: 10.1002/pc.24498
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tannin as sustainable compatibilizer for wood‐polypropylene composites

Abstract: Wood Plastic Composites (WPCs) are well‐known products which combine the high mechanical properties of wood with the high hydrophobicity and formability of polypropylene (PP). They are largely used for decking, cladding and flooring for outdoor constructions but they still present some drawbacks due to the limited chemical affinity of the two materials. In this paper, the addition of mimosa (Acacia mearnsii) tannin as compatibilizer was tested and these composites were characterized via SEM, TGA, DSC, DMA, mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 44 publications
3
13
0
Order By: Relevance
“…Fast-growing E. benthamii wood flour (W) was collected from sawing process at Embrapa Florestas (Brazil). The material was oven dried at 60 ± 5 ºC until constant mass, and then sifted between 40 -60 mesh [25] to composite preparation. The composition of the above-mentioned materials is described in Table 1.…”
Section: Raw Materials and Preparation Of Compositesmentioning
confidence: 99%
“…Fast-growing E. benthamii wood flour (W) was collected from sawing process at Embrapa Florestas (Brazil). The material was oven dried at 60 ± 5 ºC until constant mass, and then sifted between 40 -60 mesh [25] to composite preparation. The composition of the above-mentioned materials is described in Table 1.…”
Section: Raw Materials and Preparation Of Compositesmentioning
confidence: 99%
“…When tannin was embedded within the nanofibrillated cellulose, the resulting film showed highly antioxidant activity when in contact with water, and this may also represent a certain protection against fungi (YAMAGUCHI et al, 2002;PIZZI et al, 2004;TONDI et al, 2013b;MISSIO et al, 2017b). It was observed that nanocellulose films impregnated with tannin result in a film surface that is more hydrophobic than pure nanocellulose films, which is due to an intimate interconnection between the flavonoid tannin and the cellulose (MISSIO et al, 2018). Such a new, naturally derived material represents one of the most promising "active packaging" materials with antioxidant properties (OLEJAR et al, 2014;ZHOU et al, 2016).…”
Section: Wood-plastic Compositesmentioning
confidence: 99%
“…Mimosa tannin extracts are obtained through hot water extraction of bark chips in a counter-current series of autoclaves, using different parameters of temperature, pressure and time according to the required final properties of the extract (ARBENZ;AVEROUS, 2015;MISSIO et al, 2017b;MISSIO et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Condensed tannins or proanthocyanidins are phenolic compounds consisting of several types of flavan-3-ols and flavan-3,4-diols; they are polymers that are linked by carbon-carbon bonds between flavanols subunits (Schofield et al 2001;Waghorn and McNabb 2003). Many studies have investigated the replacement of phenol with tannins in phenol-formaldehydetype adhesives (Zhu et al 2012;Feng et al 2015;Li et al 2016;Anwer and Naguib 2017;Lan et al 2017;Li et al 2018;Missio et al 2018). Tannin powder has been traditionally dissolved in phenol for reactivation.…”
Section: Introductionmentioning
confidence: 99%